Large mines and the community : socioeconomic and environmental effects in Latin America, Canada, and Spain - McMahon, Gary, 1953-; Remy, Felix; World Bank.; International Development Research Centre (Canada). (Washington, DC : World Bank, 2001)
In this book, researchers from Bolivia, Chile, and Peru present and analyze the environmental, cultural, and socioeconomic effects of large mining operations in their respective countries, as well as the processes that led to the observed effects.
"International Development Research Centre."
Includes bibliographical references.
oif 27/10/15
Loan
Keywords: Mineral industries -- Latin America -- Case studies; Mineral industries -- Canada -- Case studies; Mineral industries -- Canada -- Case studies; Mineral industries -- Environmental aspects -- Latin America -- Case studies; Mineral industries -- Environmental aspects -- Canada -- Case studies; Mineral industries -- Environmental aspects -- Spain -- Case studies